Out-gassing of CO[2] from Siberian Shelf seas by terrestrial organic matter decomposition; Geophysical Research Letters; Vol. 36, iss. 20 - Anderson L. G.; Jutterström S.; Hjalmarsson S.; Wålström I.; Semiletov I. P. Igor Petrovich (2009, 2009)
Title screen